Common fixed point of a power graphic (F,psi)-contraction pair on partial b-metric spaces with application - Singh, Deepak; Chauhan, Varsha; Altun, Ishak (Nonlinear Analysis: Modelling and Control, 2017)
The aim of this paper is to inaugurate power graphic (F,ψ)-contraction pair and to establish fixed point results for such mappings defined on partial b-metric spaces endowed with a graph. It is mentioning that, first time, we launch a class of fixed point results in the frame of partial b-metric spaces involving a graph. Results of this paper extend and generalize known results from metric, partial metric, and partial b-metric spaces in partial b-metric spaces with a graph. Further, appropriate examples are presented to emphasize the utility of the obtained results. At the end, an attempt to correlate the given work with application is turned out as solution for an integral equation.